1997
DOI: 10.1536/ihj.38.393
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Accuracy of Indirect Blood Pressure Measurements.

Abstract: SUMMARYThis study assessed the accuracy of indirect blood pressure (BP) measurements by simultaneously performing three kinds of indirect BP measurement on the left arm (auscultatory, microphone and oscillometric methods) and a direct BP measurement on the left arm. The subjects were 34 hospitalized patients, ranging in age from 18 to 73 years (average 47.5 years). Highly significant correlations in systolic or diastolic BP between a given pair of the three indirect methods. The indirect methods underestimated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
17
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 20 publications
3
17
0
Order By: Relevance
“…of 10.5/7.6 mm Hg (SBP/DBP), 9.7/8.9 mm Hg and 8.1/6.5 mm Hg with the oscillometric method, microphone method and the auscultatory method, respectively. 26 In this study, the accuracy of the oscillometric blood pressure monitor was reasonably good as shown by s.d. for SBP/DBP of 7.2/ 6.1 mm Hg at steady state and 9.7/8.1 mm Hg after NTG administration, respectively (Table 2).…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…of 10.5/7.6 mm Hg (SBP/DBP), 9.7/8.9 mm Hg and 8.1/6.5 mm Hg with the oscillometric method, microphone method and the auscultatory method, respectively. 26 In this study, the accuracy of the oscillometric blood pressure monitor was reasonably good as shown by s.d. for SBP/DBP of 7.2/ 6.1 mm Hg at steady state and 9.7/8.1 mm Hg after NTG administration, respectively (Table 2).…”
Section: Discussionsupporting
confidence: 59%
“…14,24 Large variations between the indirect and direct blood pressure measurements have been well recognized. [25][26][27][28] A previous study assessing the accuracy of indirect blood pressure measurements at steady state clearly showed that the indirect methods underestimated SBP and overestimated DBP compared with the direct method, with s.d. of 10.5/7.6 mm Hg (SBP/DBP), 9.7/8.9 mm Hg and 8.1/6.5 mm Hg with the oscillometric method, microphone method and the auscultatory method, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could prevent the propagation of Korotkoff sounds to the distal auscultation site. This assumption is supported by a study of Ochiai et al, 22 who compared intra-arterially measured blood pressures with those obtained simultaneously by auscultation in the cubital fossa. They found that as well the systolic and the diastolic differences between both methods (auscultation-invasive) were positively correlated to the subject's age, probably due to fading compressibility of the arteries with increasing age.…”
Section: Discussionmentioning
confidence: 79%
“…(3) When testing the automatic devices, the relevant characteristics of the patients included in the trial, such as their age [6][7][8] and range of blood pressure, 9 must be representative.…”
mentioning
confidence: 99%